2004
DOI: 10.1007/s00421-004-1210-6
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography for examination of skin temperature in the dorsal hand of office workers

Abstract: Reduced blood flow may contribute to the pathophysiology of upper extremity musculoskeletal disorders (UEMSD), such as tendinitis and carpal tunnel syndrome. The study objective was to characterize potential differences in cutaneous temperature, among three groups of office workers assessed by dynamic thermography following a 9-min typing challenge: those with UEMSD, with ( n=6) or without ( n=10) cold hands exacerbated by keyboard use, and control subjects ( n=12). Temperature images of the metacarpal region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 19 publications
1
40
0
7
Order By: Relevance
“…[21][22][23][24][25] The advantages of thermographic cameras are that they are noninvasive and can be used without being in contact with the skin. The aim of this placebo-controlled study was to investigate the effect on skin temperature in healthy volunteers of differing skin color, age, and gender during irradiation with doses recommended in the World Association for Laser Therapy (WALT) guidelines from two commercially available therapeutic infrared class 3B lasers.…”
mentioning
confidence: 99%
“…[21][22][23][24][25] The advantages of thermographic cameras are that they are noninvasive and can be used without being in contact with the skin. The aim of this placebo-controlled study was to investigate the effect on skin temperature in healthy volunteers of differing skin color, age, and gender during irradiation with doses recommended in the World Association for Laser Therapy (WALT) guidelines from two commercially available therapeutic infrared class 3B lasers.…”
mentioning
confidence: 99%
“…This finding of systemic changes in RSI raises an important question related to the mechanism of RSI. Studies have reported impaired vascular responses after typing in the affected arm of patients with RSI (evidenced by a lower hand temperature) 6,26 and after a brief application of an ice pack to the C7 area of the cervical spine. 9 Although no direct evidence was provided, these changes were hypothesized to relate to inappropriate reflex vasodilatation, possibly via the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,26 Nonetheless, previous studies have typically examined muscular or vascular adaptations of the affected side only.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors measured skin temperatures during exercise in different parts of the human body: dorsal hand during office work [1], total body during running exercise [1], dorsal hand during cycling exercise [2], seven area on trunk during breathing exercise [3] and calves during resistance exercise [4]. These studies focused on the skin temperature response to physical exercise in different categories of subjects such as trained/untrained and old/young.…”
Section: Introductionmentioning
confidence: 99%